Flexibility in supply chain using coordination: Issues and learnings - Kaur, Arshinder (2012)
Flexibility has a variety of dimensions attached with it. In the context of supply chain (SC), flexibility needs to be defined. In this paper, an attempt is made to describe various connotations attached with the flexibility, possible sources of variability and a proposed model on coordination by contracts. The contracts offer opportunities in implementing and measuring flexibility in SCs. Supply chain flexibility (SCF) measurement is presented while coordinating the SC. An analytical model based on newsboy problem is developed to understand implications of flexibility in a three-level SC. The proposed framework may act as a decision-making tool for selecting contracts for a particular type of demand based on a number of scenarios (varying price, cost and time period) generated. This framework may help SC members to decide which contract is beneficial under various situations of uncertainty. This paper has proposed a framework which by adopting SC contracts can be an indicator of SCF which can bear variability. Copyright © 2012 Inderscience Enterprises Ltd.